2019
DOI: 10.1111/jfb.13912
|View full text |Cite
|
Sign up to set email alerts
|

Sperm maturation and male tactic‐specific differences in ejaculates in the plainfin midshipman fishPorichthys notatus

Abstract: Using the plainfin midshipman fish Porichthys notatus, a species with alternative reproductive tactics (ARTs), we investigated how sperm maturation shapes sperm competitive abilities. We compared sperm performance and morphology before and after final sperm maturation by sampling sperm from the testes and stripped ejaculates of guarders and sneakers. In accordance with sperm competition risk theory, ejaculates from sneaker males had three times as much sperm as ejaculates from guarder males and sneaker males p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…This may be explained either by a true lack of difference between male tactics, as found in several other species of fish and other taxa (reviewed in Kustra & Alonzo, 2020 ), or be a result of our sampling method, that is, sourcing the sperm directly from the testes and not as part of a stripped ejaculate. A study of the plainfin midshipman ( Porichthys notatus ) found that sperm that were sampled from ejaculates were larger in size (head and midpiece) than sperm from the testes (Miller et al, 2019 ). Nonetheless, based on a multivariate analysis, the morphological traits of plainfin midshipman sperm did not differ between dominant and sneaker males (Miller et al, 2019 ), a finding similar to our own.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained either by a true lack of difference between male tactics, as found in several other species of fish and other taxa (reviewed in Kustra & Alonzo, 2020 ), or be a result of our sampling method, that is, sourcing the sperm directly from the testes and not as part of a stripped ejaculate. A study of the plainfin midshipman ( Porichthys notatus ) found that sperm that were sampled from ejaculates were larger in size (head and midpiece) than sperm from the testes (Miller et al, 2019 ). Nonetheless, based on a multivariate analysis, the morphological traits of plainfin midshipman sperm did not differ between dominant and sneaker males (Miller et al, 2019 ), a finding similar to our own.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the plainfin midshipman ( Porichthys notatus ) found that sperm that were sampled from ejaculates were larger in size (head and midpiece) than sperm from the testes (Miller et al, 2019 ). Nonetheless, based on a multivariate analysis, the morphological traits of plainfin midshipman sperm did not differ between dominant and sneaker males (Miller et al, 2019 ), a finding similar to our own. In other fish species, differences in sperm shape can be found between male morphs.…”
Section: Discussionmentioning
confidence: 99%
“…The testes of the ocellated wrasse do not have any obvious accessory gland structures (which are rare in fishes and have to our knowledge not been reported in this group of fishes, i.e., the Labrines or family Labridae). For comparison, in midshipman, parental guarding males invest more in accessory glands and related structures that produce seminal fluid, and the seminal fluid they produce increases the velocity of guarder male sperm relative to (noncooperative) sneaker male types [28,29]. Sneaker male ejaculates in midshipman (which experience higher sperm competition than parental males) have more sperm but less seminal fluid than guarding males.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, sperm cells are one of the most diverse and rapidly evolving cells in the animal kingdom [10,11], and divergence in seminal fluid proteins contributes to reproductive isolation and therefore speciation and biodiversity [12][13][14]. Not only do sperm and other ejaculate traits diverge among populations and species [4,9,[15][16][17][18], these traits also differ among individuals in the same population [3,[19][20][21][22][23], and even change over the lifetime of an individual in response 2 of 18 to their experience, condition, and social environment [24][25][26][27][28][29][30]. All else being equal, sperm velocity, motility and longevity are expected to be higher in species with more frequent and intense sperm competition [31,32] and for individuals within species that experience chronically higher sperm competition [1,2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Além de influenciarem a produção e transferência de gametas de forma desigual, pressões assimétricas de competição espermática entre machos que adotam táticas alternativas de reprodução também podem ser responsáveis pela evolução de espermatozoides qualitativamente diferentes entre indivíduos da mesma espécie (e.g., Taborsky et al 2018;Kustra & Alonzo, 2020). Machos oportunistas podem investir em espermatozoides de maior qualidade, em termos de performance ou competitividade (e.g., mobilidade, Miller et al 2019;longevidade, Ota et al 2010; proporção de espermatozoides móveis, Locatello et al 2007), como uma forma de sobrepujar sua desvantagem comportamental. No peixe Lepomis macrochirus, por exemplo, espermatozoides de machos 'sneakers' contêm maiores reservas energéticas e atingem maiores velocidades do que gametas de machos parentais (Burness et al 2004).…”
Section: Competição Espermáticaunclassified